Правові вимоги до процедури внесення змін до Конституції України - Рудик, Петро Андрійович (My University, 2014)
На основі сучасного праворозуміння, новітніх досягнень вітчизняної науки конституційного права, його найновіших джерел, аналізу положень Конституції і законів України зроблено спробу розкрити правові вимоги до процедури внесення змін до Основного Закону держави та її етапи. On the basis of modern legal thinking, the latest achievements of the national science of constitutional law, the newest sources of this law, as well as an analysis of the Constitution and the laws of Ukraine, legal requirements for the procedure for amending the Basic Law ofthe state are examined. The stages of this procedure are presented. The comparative analysis of proper procedures concerning the Constitution and laws of Ukraine is made.
Keywords: Конституція України; правові вимоги; Constitution of Ukraine; legal requirements; кафедра економіки і права